MENINGKATKAN KOSAKATA BAHASA INGGRIS SISWA SD - Buasim Buasim (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
Mastering vocabulary is one of the essential competencies in using any language and developing vocabulary in a foreign language becomes one of the problems faced by the teacher in teaching a foreign language particulary for the beginners. Based on the existing problems and condition, this action research attempted to solve the problem. The research took place in a Government Primary School located in Tegal Parang, Jakarta, named SDN Tegal Parang 06 Pagi, Mampang Prapatan. The researcher overcame the problem in developing English vocabulary of the fourth grade of the school by using songs and media. After three cycles of practicing the action research procedures and steps, the English vocabulary of the studens was improved significantly. This research concludes, using songs and appropriate media can overcome the difficulties in developing the fourth grade students’ vocabulary in SDN Tegal Parang 06 Pagi.